(untitled) (Fiep Bulletin - online, 2019)
The aim of this study is to reflect on what it means to be a teacher in our current society. We discuss, as our theoreticalframework, Sennett’s and Bauman’s ideas regarding the principles of flexibility and of precariousness. The empirical researchfield for this study is the Lions Club public school, located in the city of Teresopolis, in Rio de Janeiro State. We have consideredthe speech extracts of three school teachers. Data were collected from the production of a written text based on the followingquestion: what does it mean to be a teacher in our current society? The results show the need of teachers to constantly reinventthemselves, to be creative and to be capable of coping with the rapid changes in their work environment. We conclude thatteaching is highlighted insofar as this act is included in the act of learning, and directly related to structuring knowledge in teachereducation.